An Integrated Analysis of Inflammatory Endotypes and Clinical Characteristics in Chronic Rhinosinusitis with Nasal Polyps - Hao D; Wu Y; Li P; Li C; Jiang T; Zhang Q; Liu S; Shi L (Dove Medical Press, 2022)
Dingqian Hao, Yisha Wu, Ping Li, Chunhao Li, Tianjiao Jiang, Qian Zhang, Shengyang Liu, Li Shi Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Li Shi; Shengyang Liu, Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Jinan, Shandong, 250000, People's Republic of China, Email shili126@sina.com; 454415082@qq.comObjective: Chronic rhinosinusitis with nasal polyps (CRSwNP) is mainly characterised by type 1 (T1), type 2 (T2) and type 3 (T3) inflammatory endotypes. However, correlations between inflammatory endotypes and clinical features in CRSwNP have not been demonstrated sufficiently. This study aimed to determine the endotype-phenotype associations in CRSwNP.Methods: Clinical data of 31 control subjects and 106 CRSwNP patients were analysed. Interferon (IFN)-γ (T1), Charcot-Leyden crystal galectin (CLC) (T2) and Interleukin (IL)-17A (T3) were used as biomarkers to identify the inflammatory endotypes.Results: The mRNA expression level of IFN-γ was positively correlated with IL-17A (r = 0.817; P < 0.0001). Headache/facial pain (P = 0.039) was associated with T1 endotype. Smell loss (P = 0.025) was associated with T2 endotype. Purulent rhinorrhea (P = 0.001) was associated with T3 endotype. Atopy (P = 0.030), asthma (P = 0.005) and recurrence (P = 0.022) were more frequent in T2 endotype. Total Symptom Scores (TSS) of T2 (P < 0.001) and T3 (P = 0.009) endotype were higher than non-T2 and non-T3, respectively. Sino Nasal Outcome Test-22 (SNOT-22) total scores of T3 (P = 0.054) endotype were higher than non-T3.Conclusion: Identifications of endotype-phenotype associations are useful in clinical diagnoses and targeted therapies for patients with CRSwNP.Keywords: chronic rhinosinusitis with nasal polyps, endotype, phenotype, diagnosis, therapy